2005 Pedazo de Carne - Grupo Teatro La Cochera (2017)
Actúan: Silvina Apfelmann, marcelo asevedo, Silvina Bustos Fierro, Lalo Orellano, Hernán Rossi | Operación técnica: Fernando Castello | Dirección: Paco Giménez | Consultado el 8 de mayo de 2016 | http://www.alternativateatral.com/obra4925-pedazo-de-carne